Effects of Chrysin on Carbon Tetrachloride-Induced Testicular Damage in Rats: Biochemical, Histopathological and Immunohistochemical Evaluation - Parlak Ak, Tuba; Yaman, Mine; Tatli Seven, Pınar; Burcu, G.Ü.L.; İFlazoğlu Mutlu, Seda; Sur Arslan, Aslıhan; İsmail, Seven (Ataturk Universitesi, 2021)
The aim of this study was to evaluate the effect of chrysin on testicular damage induced by carbon tetrachloride (CCl4) in rats. Twenty-four male Spraque-Dawley rats were divided into four groups as the control group, Chrysin group, CCl4 group, and Chrysin+CCl4 group. Chrysin (100 mg/kg/body weight/day) and CCl4 (0.5 ml/kg/body weight/day in corn oil (1:1)) were administered by gavage for 14 days. Compared to the control group, it was determined that malondialdehyde (MDA) level increased, reduced glutathione (GSH) level, and superoxide dismutase (SOD) and catalase (KAT) activities decreased in the CCl4 group. It was also determined that many testicular lesions were induced, Johnsen’s Mean Testicular Biopsy Score (JMTBS) decreased, and caspase-3 immunoreactivity increased in this group. Compared to the CCl4 group, it was determined that GSH level and SOD and CAT activities increased, MDA level decreased in the Chrysin+CCl4 group. It was also observed that testicular lesions were alleviated, JMTBS increased, and caspase-3 immunoreactivity was decreased in this group. As a result, it was concluded that chrysin might have beneficial effects in the treatment of CCl4-induced testicular toxicity as a result of its antioxidant and anti-apoptotic properties. © 2021 Ataturk Universitesi. All rights reserved.
Ratlarda Karbon Tetraklorür Kaynaklı Testis Hasarı Üzerine Krisinin Etkileri: Biyokimyasal, Histopatolojik ve İmmunohistokimyasal Değerlendirme
Keywords: Apoptosis; Carbon tetrachloride; Chrysin; Oxidative stress; Testis